Reform Trends in Scandinavia - Eva Smith (Washington University Global Studies Law Review, 2005)
The events of September 11, 2001 had a significant impact on criminal procedures in Europe, including Scandinavia. Three days after the attacks in New York, the heads of European countries in the European Union assembled and decided that they would join the War Against Terror. These remarks detail the trends in reform in Scandinavia.
Keywords: Arrest; Extradition; Legal reform; Terrorism; Warrants (Law); Denmark; Europe